Clumping of ejecta and accelerated cosmic rays in the evolution of type Ia SNRs. Issue Volume 9:Issue S296(2013) (29th January 2014) - Orlando, S.; Bocchino, F.; Miceli, M.; Petruk, O.; Pumo, M. L.
Abstract: We investigate the role played by initial clumping of ejecta and by efficient acceleration of cosmic rays (CRs) in determining the density structure of the post-shock region of a Type Ia supernova remnant (SNR) through detailed 3D MHD modeling. Our model describes the expansion of a SNR through a magnetized interstellar medium (ISM), including the initial clumping of ejecta and the effects on shock dynamics due to back-reaction of accelerated CRs. The model predictions are compared to the observations of SN 1006. We found that the back-reaction of accelerated CRs alone cannot reproduce the observed separation between the forward shock (FS) and the contact discontinuity (CD) unless the energy losses through CR acceleration and escape are very large and independent of the obliquity angle. On the contrary, the clumping of ejecta can naturally reproduce the observed small separation and the occurrence of protrusions observed in SN 1006, even without the need of accelerated CRs. We conclude that FS-CD separation is a probe of the ejecta structure at the time of explosion rather than a probe of the efficiency of CR acceleration in young SNRs.